Enhancing Brand Loyalty through Customer Satisfaction Strategies in Digital Business - Dyatmika, Sutama Wisnu; Suyanto, Bagong; Setijaningrum, Erna; Rizky, Agung; Mkhize, Thabo (Pandawan, 2025)
In the era of rapidly developing digital business, understanding the relationship between Customer Satisfaction Management Strategy (CSMS) and Brand Loyalty (BL) is crucial for a company success. Digital business platforms present unique opportunities and challenges, making it essential to explore strategies that foster strong customer relationships and loyalty. This research aims to investigate the impact of CSMS on BL in a digital business context using the SmartPLS approach. The study seeks to provide both theoretical and practical insights into the dynamics of customer satisfaction and loyalty in digital environments. Data was collected through online surveys of customers from various digital business platforms. The analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS, which is particularly suited for examining complex relationships between latent variables. The results of the analysis show that there is a significant relationship between CSMS and BL. These findings highlight the importance of fostering meaningful interactions between brands and customers to enhance loyalty in digital business environments. The practical implication of this research is the necessity for companies to design marketing strategies that prioritize meeting customer needs and preferences. This approach not only strengthens customer loyalty but also equips businesses to navigate the challenges of competitive digital markets. The study contributes valuable insights for business practitioners and adds to the literature on marketing management in the ever-evolving digital era.